Brazilians sentenced to sewage-related diseases - Édison Carlos (Rev Rene)
There is no furthest behind infrastructure in Brazil than the lack of sewage disposal, particularly the shortage of services for treating water, and for collecting and treating waste. The scarcity of these essential services to human dignity has been plaguing millions of Brazilians, as indicated by the data of the National Sanitation Information System 2014. We have 35 million Brazilians without access to services for treating water, where half the population has no sewage collection and only 40% of the waste collected in this country is treated. The shortage of sewage disposal affects all of us.